Design and analysis of near infrared high sensitive metal-insulator-metal plasmonic bio-sensor. Issue 1 (February 2021) - Ben salah, H; Hocini, A; Melouki, N; Khedrouche, D
Abstract: In this paper, a high sensitivity metal-insulator-metal (MIM) waveguide based plasmonic sensor, coupled by a hexagonal ring resonator is proposed. The sensing characteristics of the device are analyzed by the finite-difference time-domain (FDTD) method embedded in the commercial simulator R-Soft. From results, there is a linear relation between the material's refractive index and its wavelength resonances. Moreover, the maximum linear sensitivity is S = 1743 nm/RIU for the second mode and it is S = 836 nm/RIU for the first mode, its corresponding sensing resolution is 5.73 × 10 −6 RIU for mode 2 and 1.19 × 10 −5 RIU for mode 1. The proposed sensor can be implemented in high performance nano-sensors and bio-sensing devices. The positions of transmission peaks can be easily manipulated by adjusting the inner side lengths of the hexagonal ring resonator, making this structure a dynamically controllable band pass filter. In addition, introducing another small hexagonal ring within the base resonator decreased the full width of half maximum (FWHM) of the resonance peak.